Identification and isolation of heavy-metal tolerant and bioaccumulator bacteria obtained from El Fraile mine tailings, Mexico - Toledo-Hernández, Erubiel; Santana-Flores, Amairani; Sánchez-Ayala, Alejandro; Romero-Ramírez, Yanet; Ortega-Acosta, Santo Ángel; Toribio-Jiménez, Jeiry (REVISTA TERRA LATINOAMERICANA, 2020)
The mining activity has left mine tailings with high quantities of heavy metals and metalloids. Due their extreme toxicity, they represent a hostile environment for microbial colonization; however, there are metalotolerant bacteria in these mining wastes, and this is attributed to mechanisms of bioaccumulation and biotransformation of metals. The native bacteria from El Fraile mine tailings have developed adaptation mechanisms that allow them to persist in a toxic environment, thus, the objective of this study was to isolate and identify bacteria with the ability to tolerate, bioaccumulate or biotransform heavy metals. Our study was based on descriptive observations, we isolated 141 strains from water, leachate, soil, and rhizosphere and stems of plants from El Fraile mine tailings, Guerrero, Mexico. Bacterial tolerance was determined by the minimum inhibitory concentration in different metallic salts, the capacity of bioaccumulation of Ag, Pb, Cr, and Cd, and by the biotransformation of As (III) and Cr6+; in addition, representative bacteria were identified using 16S rRNA gene sequences. The results of the 141 strains analyzed showed ascending tolerance to Cd2+ 2 mM, Cu2+ 5 mM, Pb2+ 9 mM, Zn2+ 9 mM, Ag2+ 10 mM, As3+ 30 mM, and As5+ 45 mM. Only 9.24 and 39% of the strains bioaccumulated Zn2+, Pb2+ and Ag2+. In regard to biotransformation, 9% oxidized As3+ to As5+, and 7 and 24% reduced As5+ to As3+ and Cr6+ to Cr3+, respectively. The genera that prevailed were Chryseobacterium sp., Staphyloccoccus sp., Stenotrophomonas sp., Acinetobacter sp., Bacillus sp., Serratia sp., and Enterobacter sp. These results showed that in El Fraile mine tailings, there are bacterial strains capable of bioaccumulating and biotransforming heavy metals and metalloids; therefore, further studies must be conducted to know their potential in the processes of bioremediation of areas polluted with metals.